Test The Toxicity of The Ethanol Extract of Lacum Leaves (Cayratia trifolia L.) Using The Brine Shrimp Lethality Test (BSLT) Method - Cuthadisti Arhafna; Tri Mustika Sarjani; Ekariana S. Pandia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
People use the lacum plant (Cayratia trifolia L.), an herbaceous plant from the Vitaceae family that grows wild, as a traditional medicine. Lacum leaves have special things inside them called secondary metabolites like flavonoids, alkaloids, phenols, steroids, terpenoids, and tannins. Toxicity tests must be carried out because flavonoids, alkaloids and steroids have harmful effects on test animals at certain concentrations. A substance or natural ingredient that will be used as a medicine is tested to determine its level of toxicity. The purpose of this study was to determine the total levels of toxic compounds and the level of toxicity in the ethanol extract of lacum leaves (Cayratia trifolia L.) Brine Shrimp Lethality Test (BSLT). This research uses Artemia salina leach larvae as test subjects. This research also used an experimental approach arranged in a completely randomized design (CRD) consisting of 7 treatments and 4 replications. The percentage of larval death was used in probit analysis to identify the toxic effects of the extract and calculate the LC50 value. Based on the research results, it shows that there are total levels of toxic compounds in the ethanol extract of lacum leaves (Cayratia trifolia L.), namely flavonoids, alkaloids and steroids with an LC50 value of 105.08 ppm which places it in the moderately toxic category and is thought to have anticancer properties.